2009
DOI: 10.1017/s0021932009990137
|View full text |Cite
|
Sign up to set email alerts
|

Hiv Serostatus Disclosure Pattern Among Pregnant Women in Enugu, Nigeria

Abstract: This study was carried out in two medical facilities in Enugu, Nigeria, from September to November 2007. An interviewer-administered questionnaire was used to collect data from HIV-positive pregnant women accessing PMTCT (prevention of maternal-to-child transmission) services at the two centres. Ninety-two women were interviewed: 89 (96.7%) had disclosed their status, while 3 (3.3%) had not. Of the 89 women who had disclosed, 84 (94.4%) had disclosed to partners, 82 (92.1%) to husbands, 2 (2.2%) to fiancés, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…Th is fi gure is comparable to recently published data from tertiary health facilities in Nigeria (Akani and Erhabor 2006;Ezegwui et al 2009) and sub-Saharan Africa (Deribe et al 2008;Varga et al 2006). However, an earlier review on HIV serostatus disclosure among women in developing countries reported a range of 14 -83.3% (Medley et al 2004).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Th is fi gure is comparable to recently published data from tertiary health facilities in Nigeria (Akani and Erhabor 2006;Ezegwui et al 2009) and sub-Saharan Africa (Deribe et al 2008;Varga et al 2006). However, an earlier review on HIV serostatus disclosure among women in developing countries reported a range of 14 -83.3% (Medley et al 2004).…”
Section: Discussionsupporting
confidence: 87%
“…In Nigeria, published data indicate that between 77% and 96% of adult HIV-positive persons disclose their serostatus to their sexual partners (Akani and Erhabor 2006;Ezegwui et al 2009) Th e fear of stigmatisation and victimisation arising from disclosure of HIV-positive serostatus has been associated with the non-disclosure of HIV status (Akani and Erhabor 2006;Ezegwui et al 2009;Mohammed and Kissinger 2006;Sagay et al 2006a). In addition, non-disclosure is also more likely to occur when the sexual partner is seronegative (Mohammed and Kissinger 2006 (Sagay et al 2006b) from our institution indicate that up to 80% of HIV seropositive pregnant women have sexual partners that are seronegative, a situation that is likely to heighten the risks of non-disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…About 73% of our study participants reported a supportive or understanding initial partner reaction to disclosure. Although there are differences in study population, this high rate of supportive reactions to disclosure is similar to other studies among pregnant women in Jos 13 and Enugu 9 States in Nigeria where 90% and 63% of the women respectively reported supportive partner reactions to disclosure. Other comparable studies conducted in Burkina Faso, Tanzania, Kenya, Ethiopia and United States of America also reported predominant supportive partner reactions of 62-92%.…”
Section: Discussionsupporting
confidence: 85%
“…12 Failure to disclose has been attributed to fear of abandonment, broken relationships, physical and emotional abuse, discrimination and loss of economic support. 2 Despite these disclosure-related fears, studies from both developed and developing countries [2][3][4][5][6][7] , Nigeria inclusive [8][9][10][11][12][13] , have revealed predominant positive or supportive reactions to disclosure, with 50-100% of sexual partners eliciting positive reactions following disclosure. The few reports of negative reactions such as disruption of relationships, violence and discrimination were more commonly reported among unmarried sexual partners and sero-discordant couples, as well as among people from low economic status and in those with history of violence in their relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation